2017
DOI: 10.1103/physrevb.96.024303
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational dynamics of a two-dimensional microgranular crystal

Abstract: We study the dynamics of an ordered hexagonal monolayer of polystyrene microspheres adhered to a glass substrate coated with a thin aluminum layer. A laser-induced transient grating technique is employed to generate and detect three types of acoustic modes across the entire Brillouin zone in the −K direction: low-frequency contact-based modes of the granular monolayer, high-frequency modes originating from spheroidal vibrations of the microspheres, and surface Rayleigh waves. The dispersion relation of contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…This effect was first investigated in the sub‐gigahertz regime by the pump‐probe transient grating (TG) technique and time‐domain imaging in PnCs made out of self‐assembled silica microspheres adhered to an aluminium‐coated glass substrate. Recent follow up of the TG study has revealed additional features in the gigahertz range such as contact‐induced splitting of the vibrational modes of nanoparticles and the interaction of these modes with Rayleigh SAWs . Theoretically, this type of SAW PnCs offers all three schemes for bandgap opening, whereas the period and local resonances can be adjusted by the size and material of nanoparticles, contact resonances can be tailored by the particle–substrate adhesion by means of surface physics or chemistry …”
Section: Surface and Membrane Hypersonic 2d Pncsmentioning
confidence: 99%
“…This effect was first investigated in the sub‐gigahertz regime by the pump‐probe transient grating (TG) technique and time‐domain imaging in PnCs made out of self‐assembled silica microspheres adhered to an aluminium‐coated glass substrate. Recent follow up of the TG study has revealed additional features in the gigahertz range such as contact‐induced splitting of the vibrational modes of nanoparticles and the interaction of these modes with Rayleigh SAWs . Theoretically, this type of SAW PnCs offers all three schemes for bandgap opening, whereas the period and local resonances can be adjusted by the size and material of nanoparticles, contact resonances can be tailored by the particle–substrate adhesion by means of surface physics or chemistry …”
Section: Surface and Membrane Hypersonic 2d Pncsmentioning
confidence: 99%
“…The complexity of the time-domain modes shapes (see inset of 2e) suggests that the gaps we observe originate from the hybridization of the propagating SAW with an abundance of closely-spaced multi-resonant modes (both flexural and compressional), similar to what has been observed for Lamb waves in macroscale inorganic locally resonant acoustic metamaterials. 53 We note that, in contrast to typically locally resonant metamaterials where the resonators are uncoupled, because of the inter-resonator connectivity (corresponding to the beehive structure) in the physical sample, we expect the hybrid mode with a horizontally-asymptotic branch induced by local resonances to revert to a propagating mode with a non-zero dispersion curve at high k. 54 The multiresonant nature of the ridges could be leveraged to realize locallyresonant metamaterials that have increased tunability with minimal structural complexity, in comparison to phononic crystals or metamaterials having a single local resonance. The structure of plants, which is one element of their phenotype, can be controlled by environmental or genetic cues.…”
mentioning
confidence: 94%
“…In this context photoacoustic nanometrology plays a key role. For instance, the bulk properties of periodic nanogranular thin films have been explored across a variety of configurations [13,14] ranging from 1D [15], 2D [16][17][18][19][20][21][22] to 3D [23,24] arrangements. Recently, the development of table-top UV laser sources allowed generating surface acoustic waves with periodicity in the 10 nm range [25], hence opening to mechanical nanometrology [26] of periodic granular thin films of thicknesses down to few nanometers [27,28].…”
Section: Introductionmentioning
confidence: 99%